Roles of each leg in impulse generation in professional baseball pitchers: preliminary findings uncover the contribution of the back leg towards whole-body rotation - Liu, J. M.; Knowlton, C.; Gauthier, M.; Tropp, Z.; Verma, N.; Nicholson, G.; Romeo, A.; Zaferiou, A. (Sports Biomechanics, 2022)
This study examined the roles of each leg in generating linear and angular impulses during baseball pitching. Professional pitchers (n = 4) pitched from a force plate instrumented mound, and 6-11 successful fastball pitches were used for analyses. We compared linear and angular impulses across the back and front legs. Linear and angular impulses were calculated from ground reaction force (GRF) and moment about each global axis passing through the centre of mass (COM), respectively. Additionally, we analysed measures that control the moment: (1) GRF magnitude, (2) magnitude of the position vector from COM to the centre of pressure and (3) the angle between (1) and (2). We found that the back leg generated forward linear impulse and the front leg generated backward linear impulse for all pitchers. Surprisingly, we found that the back leg generated significantly greater positive angular impulse about a global leftward axis (from the mound towards first base) than did the front leg in all four pitchers. Furthermore, the back leg`s moment about the leftward axis became positive after the magnitude of forward GRF decreased from its maximum, suggesting that the back leg`s role transitioned from generating forward linear momentum to angular momentum.